The concept of religious pluralism in Indonesia: a study of the MUIâs fatwa and the debate among Muslim scholars - Basya, Muhammad Hilaly (State Institute of Islamic Studies (STAIN) Salatiga, 2011)
In 2005 The Council of Indonesian Ulama (MUI) issued a controversial fatwa. Thefatwa states that it is prohibited for Muslims to develop the ideas of religiouspluralism. The fatwa had provoked heat debate among Indonesian Muslim scholars.For the opponent of the fatwa, the modern Indonesian state should be supportedby the ideas of pluralism. They are disappointed with the fatwa, since itwould diminish religious pluralism in Indonesia. On the other hand, the protagonistof the fatwa said that the MUI has done good decision. The ideas of pluralismare seen by them would threaten Islamic faith. They believed that those whocampaigned for the idea of pluralism are the agent for âwesternâ interest. Thedebate regarding the MUIâs fatwa banning Muslims to adopt pluralism ideas indicatesthat the concept of pluralism campaigned by some Muslim scholars is notmonolithic. This paper would like to explore various conceptions of religious pluralismamong Indonesian Muslim scholars.Pada 2005, Majelis Ulama Indonesia (MUI) mengeluarkan sebuah fatwakontroversial. Fatwa itu menyatakan haram hukumnya bagi kaum Muslim untukmengembangkan gagasan-gagasan tentang pluralisme agama. Fatwa telahmengundang perdebatan panas di kalangan sarjana Muslim Indonesia. Bagi parapenentang fatwa, Negara Indonesia modern harus didukung dengan gagasanpluralisme. Mereka kecewa atas fatwa karena telah mengurangi pluralismekeagamaan di Indonesia. Di sisi lain, para pendukung fatwa menyatakan bahwaMUI telah mengeluarkan keputusan yang benar. Bagi mereka, gagasan pluralismeakan mengancam keimanan Islam. Mereka yakin bahwa orang-orang yangmengampanyekan gagasan tentang pluralisme merupakan agen kepentinganBarat. Perdebatan mengenai fatwa MUI yang melarang kaum Muslim mengadopsigagasan pluralisme menunjukkan bahwa konsep pluralisme yang dikampanyekansebagian sarjana Muslim tidaklah monolitik. Kajian ini akan mengeksplorasiberbagai konsep pluralisme keagamaan di kalangan sarjana Muslim Indonesia.Â